2003
DOI: 10.1016/s0928-8244(03)00070-1
|View full text |Cite
|
Sign up to set email alerts
|

Construction of recombinant S-layer proteins (rSbsA) and their expression in bacterial ghosts – a delivery system for the nontypeableHaemophilus influenzaeantigenOmp26

Abstract: This study has investigated the feasibility of a combination of recombinant surface layer (S-layer) proteins and empty bacterial cell envelopes (ghosts) to deliver candidate antigens for a vaccine against nontypeable Haemophilus influenzae (NTHi) infections. The S-layer gene sbsA from Bacillus stearothermophilus PV72 was used for the construction of fusion proteins. Fusion of maltose binding protein (MBP) to the N-terminus of SbsA allowed expression of the S-layer in the periplasm of Escherichia coli. The oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 40 publications
(68 reference statements)
0
33
0
Order By: Relevance
“…[21,29] Concerning periplasmic targeting of S-layer proteins in general, MBP has been reported to export the S-layer protein SbsA of G. stearothermophilus PV/72 to the periplasm of E. coli. [32] The different S-layer fusion proteins were expressed in E. coli BL21 Star (DE3) carrying the respective expression plasmids. Based on the masses of A_SgsE and G_SgsE of 93.7 and 61.0 kDa, respectively, the masses of the different fusion proteins were calculated to be 95.9 and 63.2 kDa for the ssPelB constructs, 139.2 and 106.5 kDa for the MBP constructs, and 98.4 and 65.7 kDa for the ssTor constructs.…”
Section: Periplasmic Targeting Of Sgsementioning
confidence: 99%
“…[21,29] Concerning periplasmic targeting of S-layer proteins in general, MBP has been reported to export the S-layer protein SbsA of G. stearothermophilus PV/72 to the periplasm of E. coli. [32] The different S-layer fusion proteins were expressed in E. coli BL21 Star (DE3) carrying the respective expression plasmids. Based on the masses of A_SgsE and G_SgsE of 93.7 and 61.0 kDa, respectively, the masses of the different fusion proteins were calculated to be 95.9 and 63.2 kDa for the ssPelB constructs, 139.2 and 106.5 kDa for the MBP constructs, and 98.4 and 65.7 kDa for the ssTor constructs.…”
Section: Periplasmic Targeting Of Sgsementioning
confidence: 99%
“…54,55 Linking MalE to SbsA the protein subunits can also be exported to the PPS prior to S-layer formation. 56 All different options of AG presentation in BG envelopes are summarized in Figure 2A as a schematic drawing.…”
mentioning
confidence: 99%
“…The maximum antibody responses were observed on week 3 post-vaccination period in Group B and C when compared to group A. It is well-documented that the SEG vaccines induce protective immunity [15]. Another study [27] demonstrated that the outer membrane proteins are important to induce protective immunity against Salmonella infections.…”
Section: Resultsmentioning
confidence: 90%
“…About 2 mL of this suspension was added to 1 mL of MIC of NaOH and was incubated at 37°C for different time points (15,30,45,60, and 70 minutes). About 25 µL of each incubated time points were cultured on LB agar plates and incubated for 24 hrs at 37°C.…”
Section: Production Of Segsmentioning
confidence: 99%
See 1 more Smart Citation